2020
DOI: 10.1108/er-10-2019-0385
|View full text |Cite
|
Sign up to set email alerts
|

Gender, diversity management perceptions, workplace happiness and organisational citizenship behaviour

Abstract: PurposeThe purpose of this paper is to investigate whether females have different perceptions of diversity management and workplace happiness compared to their male colleagues. Furthermore, the paper explores whether diversity management perceptions mediate the relationship between workplace happiness and organisational citizenship behaviour.Design/methodology/approachA total of 260 questionnaires from a number of public hospitals in Egypt were analysed using both t-test and Structural Equation Modelling.Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 99 publications
6
58
0
4
Order By: Relevance
“…However, and with specific reference to the challenging nature of some OCB such as voice behavior, it can be risky for individuals and therefore only flourishes in certain contexts [42]. The literature has shown that, in general, perceived diversity management and inclusion are positively linked to OCB [130,131]; nevertheless, previous studies have either mainly focused on the affiliative type of OCB (such as helping behaviors) (e.g., [132]) and/or they have relied on social-exchange theory as the only mechanism to explain the relationship between an organization's context for diversity and inclusion and what its employees give back in terms of OCB [133].…”
Section: Discussionmentioning
confidence: 99%
“…However, and with specific reference to the challenging nature of some OCB such as voice behavior, it can be risky for individuals and therefore only flourishes in certain contexts [42]. The literature has shown that, in general, perceived diversity management and inclusion are positively linked to OCB [130,131]; nevertheless, previous studies have either mainly focused on the affiliative type of OCB (such as helping behaviors) (e.g., [132]) and/or they have relied on social-exchange theory as the only mechanism to explain the relationship between an organization's context for diversity and inclusion and what its employees give back in terms of OCB [133].…”
Section: Discussionmentioning
confidence: 99%
“…Fisher (2010) considers workplace happiness as an attitudinal construct that involves three dimensions: engagement, job satisfaction and affective organizational commitment. Moreover, Zelenski et al (2008), Fisher (2010, Mousa et al (2020a), Mousa et al (2020b) and Erdogan et al (2012) highlight that workplace happiness comes as an outcome of workplace justice, an open communication policy, inclusive work culture and others. This explains to a large extent how both diversity management, which is concerned with workplace justice, and organizational inclusion, which promotes openness, integration and respect, are perceived as determinants or may even be drivers of workplace happiness.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has argued that happier and healthier employees increase their effort, performance and productivity (Huang et al, 2016). Similarly, research has documented that employee well-being has a positive influence on employee work-related attitudes and behaviors such as, increasing OCB (Mousa et al, 2020), as well as job performance (Magnier-Watanabe et al, 2017) and decreasing employees' work-family conflict (Karapinar et al, 2019) and absenteeism (Schaumberg and Flynn, 2017). Although there is evidence that employee well-being positively influences employee work-related attitudes, less is known about the relationship between psychological well-being (hedonic and eudaimonic) and employee affective commitment (Pan et al, 2018;Semedo et al, 2019).…”
Section: Hypotheses Development 21 Psychological Well-being and Affective Commitmentmentioning
confidence: 99%